Pre-Modern Nordic Memories in their Literary Contexts - Glauser, Jürg (Scandinavistica Vilnensis, 2023)
The study of memory has become a central field in saga scholarship in recent years. The present article deals with a number of remarkable mnemonic phenomena in Old Norse-Icelandic narratives. It contextualizes them in biblical, classical, and more modern examples of memory culture. These serve as texts of reference for the Norse narratives that are in the focus of this article. Some of the analyses are inspired by the German philosopher Hans Blumenberg’s work on how myth has always already transgressed to memory (reception) and the art historian Aby Warburg’s concept of pathos formulae that produce emotional impacts and mnemonic tropes.Aspects that are treated are for instance acts of commemoration as social and cultural activities, eddic mytho-narratives as stories to remember, the importance of the body and the senses in terms of memory studies, the interrelationship of remembrance and oblivion, and finally pre-modern mediologies. Central texts discussed in the article are eddic poems such as Völuspá (The Seeress’s Prophecy), skaldic poetry and its mnemonic pictorality, Icelandic sagas and historical writings (Icelandic Book of Settlement), examples of folklore. Some outstanding features are stellar memories, the question whether the place of memory is in the human breast or brain, or the importance of avian imagery in narratives about birds as preeminent media of remembering and forgetting.The article has a comparative approach. It attempts to show how Old Norse-Icelandic literature is closely contextualized within a web of Scandinavian and non-Scandinavian narratives and thoroughly shaped by features of cultural memory, shifting constructions of and dealings with ever changing imaginations of pasts.
Keywords: Old Norse-Icelandic literature; comparative literature; Pre-modern Nordic memory studies; remembering; oblivion; mediality; sagas; eddas; skaldic poetry